Imitation of Location Choices for Foreign Investments: The Role of Subnational Foreign Locations' Cultural Tightness - Slangen, Arjen; Valboni, Riccardo; Braito, Nazareno; Puck, Jonas (Journal of Management Studies, 2024)
Firms are known to commonly imitate peers' foreign investment location choices. We shed further light on this phenomenon by exploring the role of foreign locations' cultural tightness, which refers to the prevalence of social norms in a location and the tolerance for deviance from them. Combining institutional theory with insights from research on cultural tightness, we hypothesize that firms are more strongly inclined to imitate peers' choice for a subnational foreign investment location when the location is culturally tighter. Our hypothesis receives consistent support in conditional logit analyses based on 2900 foreign investments in new manufacturing plants in US metropolitan areas over the period 2008–2019. Furthermore, the amplifying effect of a subnational location's cultural tightness on firms' propensity to imitate their peers' choice for the location seems to depend on firms' experience with cultural tightness and their home country's cultural distance from the USA. Our findings enrich international management research on location choice imitation, legitimacy risks, and cultural tightness.